Pelatihan Pembuatan Media Pembelajaran Berbasis Augmented Reality Untuk Mengembangkan TPACK Guru Sekolah Dasar - Dessy Norma Juita; Laely Farokhah; Venna Puspita Sari (Journal of Empowerment Community, 2026)
The rapid development of digital technology in education requires elementary school teachers to integrate technological, pedagogical, and content knowledge to create engaging and meaningful learning experiences. However, many teachers still rely on conventional teaching media and lack understanding of how to utilize digital innovations such as augmented reality in classroom instruction. This community service program aimed to improve teachers’ understanding and skills in designing and implementing interactive learning media through a training program on the use of augmented reality in elementary education. The training was conducted online using a participatory approach, which included socialization, teacher training, the implementation of AR technology in elementary school learning, mentoring and evaluation, as well as program sustainability. The results showed that the training was effective in enhancing teachers’ conceptual understanding of augmented reality, increasing their confidence in applying technology, and developing their creativity in designing interactive learning activities. It can be concluded that systematic and participatory training can effectively strengthen teachers’ technological and pedagogical competencies while promoting innovative learning practices in elementary schools.